Representation of Anxiety in the Poster “قتال” on the Al Qassam Website: A Semiotic Analysis by Roland Barthes - Mahrotul Fithonah; Muassomah (Jurnal Sastra Indonesia, 2025)
The current events in Gaza, Palestine, are genocides that have claimed many lives. This triggered protests in various parts of the world. Various visual elements appeared, including the circulation of pro-Palestinian posters during the action. The poster is not only an ordinary publication medium, but it also conveys the anxiety of the Palestinian people and serves as a medium of emotional expression that reflects the community's feelings. This study analyzes the visual meaning, particularly in the symbols that represent the concept of anxiety, as depicted in the "قتال" poster on the official website of Brigadier Al Qassam, utilizing Roland Barthes' semiotic theory. The method used in this study is qualitative. The results of this study identified five symbols that represent anxiety and convey mythical meanings, derived from a unified understanding of connotations and denotations obtained from several selected respondents. Additionally, the researcher analyzed the meaning conveyed by the poster's color symbols. The existence of this color symbol can enhance the symbolic and emotional message it conveys. It was found that 12 dominant colors were found on the poster; the colors used tended to be dark shades. This creates a gloomy atmosphere that reflects sadness, destruction, and disaster.